Identification, characterization and validation of core collection of foxtail millet (Setaria italica) - CHANDER, SUBHASH; BHAT, K V; GOWDA, M V C; DIKSHIT, N (The Indian Journal of Agricultural Sciences, 2017)
Foxtail millet [Setaria italica (L.) P. Beauv.] is an important minor millet, which is drought tolerant, rich in micronutrients and grown in the marginal and rainfed regions of India. Power core software was used to develop the core collection of foxtail millet using total of 1515 germplasm accessions, emanating from 21 different countries. Eleven quantitative and 13 qualitative traits were utilized to characterize the core collection. Each qualitative and quantitative trait was divided into discrete classes and 223 core entries were selected from them. Selected core entries comprises accessions predominantly from India (75.78%). Average Shannon-Weaver diversity (0.73) and Nei’s diversity index (0.43) of core collection were higher for the entire collection indicating true representation of diversity available in the entire collection. Average polymorphism information content (PIC) value was 0.99. Core accessions were evaluated and validated using analysis of variance (ANOVA), descriptive statistics, clustering based on neighbour joining tree and principal component analysis. Accessions from Andhra Pradesh, Karnataka, Madhya Pradesh, Tamil Nadu, Uttar Pradesh and North-East Region were distributed in almost all the clusters and sub-clusters suggesting lack of discrete relationship between geographic locations and clustering pattern. Thus, a highly diverse core collection representing the diversity of entire germplasm holding from different parts of the world was identified and this can be used for foxtail millet improvement programs as well as to identify trait-specific reference collections.